2019
DOI: 10.1002/jcla.23047
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, changes in serum inflammatory factors, and clinical prevention and control measures for puerperal infection

Abstract: Background To investigate the risk factors and changes in serum inflammatory factors in puerperal infection, and propose clinical prevention measures. Methods A total of 240 subjects with suspected puerperal infection treated in our hospital from January 2017 to December 2017 were collected, among which puerperal infection was definitely diagnosed in 40 cases, and it was excluded in 40 cases. Levels of interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), and high‐sensitivity C‐reactive protein (hs‐CRP) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
1
16
0
4
Order By: Relevance
“…First, endometrial thickness is not the only factor that affects the pregnancy rate since it is influenced by many factors, such as age, endometrial receptivity, and embryo quality ( Zhao et al, 2014 ; Bu and Sun, 2015 ). Second, these studies did not take into account the effect of basal FSH, AMH, AFC, TSH, FT3, blood glucose or the E2 value on the day of the hCG injection per fresh transfer cycle when adjusting for covariates compared with our work, and previous studies have reported that these variables are related to pregnancy rates and miscarriage rates per fresh transfer cycle ( Vaegter et al, 2017 ; Song et al, 2020 ). Third, the research populations are different, and there are physiological differences between ethnic Chinese and ethnic Europeans, the physiological difference between the two ethnic groups are reflected in many aspects, such as body mass index difference, altered ovarian morphology and functional changes, Genes associated with reproduction and fertility changes, which might cause different pregnancy outcomes ( Mura et al, 1991 ; Lachance and Tishkoff, 2013 ; Dumesic et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…First, endometrial thickness is not the only factor that affects the pregnancy rate since it is influenced by many factors, such as age, endometrial receptivity, and embryo quality ( Zhao et al, 2014 ; Bu and Sun, 2015 ). Second, these studies did not take into account the effect of basal FSH, AMH, AFC, TSH, FT3, blood glucose or the E2 value on the day of the hCG injection per fresh transfer cycle when adjusting for covariates compared with our work, and previous studies have reported that these variables are related to pregnancy rates and miscarriage rates per fresh transfer cycle ( Vaegter et al, 2017 ; Song et al, 2020 ). Third, the research populations are different, and there are physiological differences between ethnic Chinese and ethnic Europeans, the physiological difference between the two ethnic groups are reflected in many aspects, such as body mass index difference, altered ovarian morphology and functional changes, Genes associated with reproduction and fertility changes, which might cause different pregnancy outcomes ( Mura et al, 1991 ; Lachance and Tishkoff, 2013 ; Dumesic et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…Some metaanalyses on live birth revealed that the GnRH-a protocol was more effective than the GnRH-ant protocol (34,35). However, we want to emphasize that retrospective trials are always associated with selection bias issues (36). Despite our attempts to screen eligible subjects according to the POSEIDON criteria and remove confounding factors, patients with good ovarian responses may have been more likely to be assigned to the GnRH-ant protocol group.…”
Section: Discussionmentioning
confidence: 97%
“…Postpartum infection: defined as reproductive tract infection occurring after delivery. 23 3. Complications of the surgical wound: defined as an abnormality in the evolution of healing, such as dehiscence and surgical site infection.…”
Section: Methodsmentioning
confidence: 99%